Analisis Perbandingan Algoritma Penjadwalan terhadap Performa Sistem Operasi Menggunakan MATLAB - Iqbal Fernando; Octoberry Julyanto; Awan Setiawan (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Process scheduling algorithms play an important role in determining the performance of operating systems, particularly in managing CPU utilization and process execution efficiency. Ineffective scheduling mechanisms can lead to increased waiting time and reduced system performance. This study aims to model and simulate several process scheduling algorithms using MATLAB in order to evaluate their performance characteristics. The research method involves developing simulation models for selected scheduling algorithms, including First Come First Serve, Shortest Job First, and Round Robin. Performance evaluation is conducted based on key parameters such as average waiting time, turnaround time, and processor throughput. The simulation results demonstrate that each scheduling algorithm exhibits different performance behaviors depending on the workload characteristics. Shortest Job First produces the lowest average waiting time, while Round Robin offers better response time fairness for time-sharing systems. The findings indicate that simulation-based analysis using MATLAB provides an effective approach to understanding the behavior and performance trade-offs of process scheduling algorithms. This research contributes as a reference for selecting appropriate scheduling algorithms in operating system design and as a learning model for process scheduling analysis.